Online teaching strategies for conversational English by university lecturers - Farisani Thomas Nephawe (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2023)
Numerous strategies for teaching conversational English online are utilised although some have less value for money due to constraints including poor connectivity, constant ‘load shedding’, and lack of computing device systems. The paper investigated a suitable strategy for teaching conversational English online to English Communication Skills students registered for Module 1141 in the 2022 academic year at the University of Venda, South Africa. A qualitative research approach was adopted as in-depth knowledge and a wide range of speech exchange systems could be obtained. Three lecturers were purposively selected from a pool of seven lecturers to participate in the paper because they were easily approachable and had been teaching the module for over five years. Data were collected using observations and semi-structured face-to-face interviews. Atlas ti version 22 software was used to analyse the data as it locates codes and interprets the findings in primary data material, weighs and evaluates their importance, and visualises the often-complex relationships between them. The pilot study results indicated that the lecturers were not comfortable with using the videoconferencing strategy for teaching conversational English online. But after showing them steps for using the identified strategy, the lecturers revealed extreme indebtedness towards the process. Using the identified strategy for teaching conversational English online is highly recommended.